Phytochemical Investigation and Antioxidative Capacity of Triterpenes Present in Plant Species Belonging to Lamiaceae Family - Jordamović, Nadir; Nikšić, Haris; Muratović, Samija; Gušić, Irma; Korić, Emina; Alagić, Larisa; Pašić, Maja; Durić, Kemal (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2020)
Triterpenes are persistently associated with observed bioactivities of extracts obtained from plant material that contains these very important natural products. Many species belonging to Lamiaceae family have been used for the presence of essential oil and very little is known about the presence of the triterpene substances in this family. Qualitative and quantitative analyses of this very important substances, in the aerial parts of eight species, all belonging to Lamiaceae family, were investigated in this study. Different extracts containing triterpene substances were tested by DPPH method to evaluate their antioxidative capacity. TLC and HPLC methods, used for the analytical determination of triterpenes, showed the presence of betulin, betulinic acid, ursolic acid and oleanolic acid. Betulin (3.2 mg/g) and betulinic acid (37.1 mg/g) were the most abundant triterpene components in the hexane extracts of Rosmarinus officinalis L. Ursolic acid (0.14 mg/g) was the most abundant triterpene compound in the hexane extract of Thymus pulegioides L. All tested samples demonstrated DPPH scavenging activity in a concentration dependant manner, with a wide range of IC50 values from 0.4 mg/mL to 3.3 mg/mL.